2019
DOI: 10.1007/s12264-019-00424-2
|View full text |Cite
|
Sign up to set email alerts
|

L-type Calcium Channels are Involved in Iron-induced Neurotoxicity in Primary Cultured Ventral Mesencephalon Neurons of Rats

Abstract: In the present study, we investigated the mechanisms underlying the mediation of iron transport by Ltype Ca 2? channels (LTCCs) in primary cultured ventral mesencephalon (VM) neurons from rats. We found that cotreatment with 100 lmol/L FeSO 4 and MPP ? (1-methyl-4phenylpyridinium) significantly increased the production of intracellular reactive oxygen species, decreased the mitochondrial transmembrane potential and increased the caspase-3 activation compared to MPP ? treatment alone. Co-treatment with 500 lmol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…FPN1 is the only known protein that controls iron output in mammalian cells, and plays a critical role in the transport of Fe 2+ and maintenance of intracellular iron balance ( Trujillo-Alonso et al, 2019 ). However, based on this regulated mechanism of precise intracellular input-transport-storage or exocytosis, any process of iron uptake, transportation, storage or utilization will cause abnormal metabolism of intracellular iron ions, resulting in abnormalities in the Fe 2+ metabolic chain, and then may lead to Fenton reaction to generate ROS ( Xu et al, 2020 ). Then, ROS subsequently modifies and interferes with proteins, lipids and DNA, and finally induces the termination of cell life ( Singh et al, 2014 ; Bogdan et al, 2016 ).…”
Section: Ferroptosismentioning
confidence: 99%
“…FPN1 is the only known protein that controls iron output in mammalian cells, and plays a critical role in the transport of Fe 2+ and maintenance of intracellular iron balance ( Trujillo-Alonso et al, 2019 ). However, based on this regulated mechanism of precise intracellular input-transport-storage or exocytosis, any process of iron uptake, transportation, storage or utilization will cause abnormal metabolism of intracellular iron ions, resulting in abnormalities in the Fe 2+ metabolic chain, and then may lead to Fenton reaction to generate ROS ( Xu et al, 2020 ). Then, ROS subsequently modifies and interferes with proteins, lipids and DNA, and finally induces the termination of cell life ( Singh et al, 2014 ; Bogdan et al, 2016 ).…”
Section: Ferroptosismentioning
confidence: 99%
“…Excess iron accumulation induced MMPs expression ( Woo et al, 2020 ). Studies have suggested that MMPs degrade the vascular basement membrane components, resulting in disruption of the BBB ( Jin et al, 2019 ), and that excess iron accumulation will initiate the Fenton reaction to generate ROS ( Xu et al, 2020 ). ROS subsequently modifies and interferes with proteins, lipids, and DNA, which can induce cell death.…”
Section: Ferroptosis In Blood-brain Barrier Degradationmentioning
confidence: 99%
“…Iron is an essential metal for normal cellular function and participates in many physiological processes, such as oxygen transport, cellular respiration, DNA synthesis, myelinization, and neurotransmitter biosynthesis in the nervous system (DeGregorio-Rocasolano et al, 2019). However, the failure of uptake, transport, storage, and utilization of intracellular iron will cause excess intracellular free Fe 2+ deposition and will initiate the Fenton reaction to generate ROS (Xu et al, 2020). Furthermore, ROS subsequently modify and interfere with proteins, lipids, and DNA, which induce cell death (Singh et al, 2014).…”
Section: Iron Metabolismmentioning
confidence: 99%